Lycopene-enriched quail egg as functional food for humans - Şahin, Nurhan; Akdemir, F.; Orhan, C.; Küçük, Ömer; Hayirli, A.; Şahin, Kazım (Elsevier, 2008)
This experiment deals with lycopene-enriched egg production in quails and their effects on antioxidant status of humans upon their consumption. Ninety Japanese quails were assigned randomly to 1 of 3 diets containing 0, 100, and 200 mg lycopene per kilogram for 90 days. Fifteen male non-smoker volunteers (30-40 years old) were given two quail eggs daily in the breakfast for 10 weeks. Dietary lycopene supplementation increased feed intake (P < 0.0003) and egg production (P < 0.001) in quails. Egg yolk colour improved (Y= 5.81 + 0.15X, R-2 =0.72, P < 0.0001), whereas egg yolk malondialdehyde (MDA) content depressed (Y=0.86-0.004X, R-2 = 0.58, P < 0.0001) as supplemental lycopene level increased. No measurable level of lycopene was detected in egg yolk of quails fed the control diet; there was a dose-dependent increase in egg yolk lycopene of quails supplemented with increasing dietary lycopene (P < 0.0001). Consumption of lycopene-enriched quail eggs was associated with increased serum lycopene (Y= 16.36 + 0.53X, R-2 = 0.82, P < 0.0001) and decreased MDA (Y = 0.76 - 0.006X, R-2 = 0.75, P < 0.0001) concentrations in humans. Moreover, there was an inverse relationship between serum lycopene and MDA concentrations (Y = 0.89 - 0.009X, R-2 = 0.61, P < 0.0001). In conclusion, dietary lycopene supplementation to quails improved performance and egg quality. Delivering lycopene via eggs quails supplemented with lycopene also increased serum lycopene and depressed serum MDA concentrations in humans. Provision of antioxidant nutrients to humans via functional food production at farm level is possible. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: lycopene; enriched egg; antioxidant; quail; human